Citalopram-induced SIADH in a hypertensive patient on salt restricted diet - TOPÇUOĞLU, VOLKAN (SAGE PUBLICATIONS LTD, 2007)
Hyponatraemia is a very rare but potentially fatal complication of SSRIs and citalopram therapy, especially during the first weeks of treatment and for those who concomitantly use medications known to cause hyponatraemia. We present a 54-year-old hypertensive female patient who was admitted to the hospital with drowsiness, paresthesia, fatigue, nausea, vomiting and visual hallucinations and who was diagnosed to have syndrome of inappropriate secretion of antidiuretic hormone (SIADH) due to citalopram. All her presenting symptoms disappeared after discontinuation of citalopram therapy, fluid restriction and a careful hypertonic saline infusion. This case suggests that SIADH may develop among hypertensive patients, especially when they use diuretics or follow a salt restricted diet.
Keywords: citalopram; SIADH; hyponatraemia; diet; SEROTONIN REUPTAKE INHIBITORS; HYPONATREMIA; SERTRALINE; FLUOXETINE; SECRETION; VASOPRESSIN; PAROXETINE